A Real-Time Sensor Based Hand Gesture Controlled Robotic Wheelchair for Assisting People with Disabilities - Rahaman, Muhammad Aminur; Islam, Md Jahidul; Kabir, Sumaiya; Khatun, Ayesha (GUB Journal of Science and Engineering, 2021)
Currently, thousands of people are suffering from paralysis. They have difficulties with speaking and walking. So we’ve developed a new kind of robot that can help those people who can’t walk or speak. By utilizing this robot (hand gloves or wheelchair handle) and gesture-based regulators, people with physical disabilities will improve their quality of life. The robot of the proposal has two components, one is the controller of the motion, and the other is the Robotic Wheelchair (RW). Where one can easily interact with the robotic-base wheelchair-using sensor-based hand gesture. With this human-robot interaction, a patient can quite easily control the robot and can move freely. In addition, the required patients may use gestures (hand gloves or wheelchair handle) to express their needs. Furthermore, we will reduce the effort to regulate the RW and hand movements with this device, that’s really difficult for disabled or dumb people. Our device can run with approximately 94% accuracy and very minimal delay. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 7, Dec 2020 P 85-93